1992
DOI: 10.1016/0741-5214(92)90249-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of lower extremity arterial duplex mapping

Abstract: We performed lower extremity arterial duplex mapping from the aortic bifurcation to the ankle in 150 consecutive patients evaluated for aortic and lower extremity arterial reconstruction and compared lower extremity arterial duplex mapping in a blinded fashion to angiography. On the basis of history, physical examination, and four-cuff segmental Doppler pressures individual lower extremities were classified as normal, isolated aortoiliac disease, infrainguinal disease, and multilevel inflow and outflow disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(94 citation statements)
references
References 10 publications
1
90
0
3
Order By: Relevance
“…60 Duplex ultrasonography is an accurate method for determining the degree of stenosis or length of occlusion of the arteries supplying the lower extremity. [61][62][63] Furthermore, duplex ultrasonography may be useful in the follow-up of patients who have undergone endovascular (percutaneous transluminal angioplasty/stent) or surgical revascularization. Some clinicians routinely place their patients into an ultrasound surveillance program after angioplasty or stent implantation, and most surgeons do so after lower-extremity bypass surgery.…”
Section: Diagnostic Evaluation Exercise Treadmill Testing and Abimentioning
confidence: 99%
“…60 Duplex ultrasonography is an accurate method for determining the degree of stenosis or length of occlusion of the arteries supplying the lower extremity. [61][62][63] Furthermore, duplex ultrasonography may be useful in the follow-up of patients who have undergone endovascular (percutaneous transluminal angioplasty/stent) or surgical revascularization. Some clinicians routinely place their patients into an ultrasound surveillance program after angioplasty or stent implantation, and most surgeons do so after lower-extremity bypass surgery.…”
Section: Diagnostic Evaluation Exercise Treadmill Testing and Abimentioning
confidence: 99%
“…However, the accuracy of waveform analysis alone in assessing the severity of lower-limb arterial disease is uncertain (12,13).…”
mentioning
confidence: 99%
“…Endothelial dysfunction and atherosclerosis of blood vessels that supply the penis are associated with the same cardiovascular risk factors (smoking, diabetes mellitus, hypertension and hyperlipidemia) which affect coronary arteries. 11,15,16 It has been reported that transforming growth factor-b1 and its type II receptor are significantly more noticeable in the cavernous tissue of patients with vasculogenic ED than they are in control subjects or psychogenic ED and that their prominence correlates with the degree of fibrosis of the cavernous tissue as shown by the abundance of collagen fibers following the percutaneous cavernous biopsy. 17 Patients with cardiovascular disease run more risks of developing ED.…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical atherosclerosis was defined by the presence of established cardiovascular risk factors (age, hypertension, diabetes, hyperlipidemia and cigarette smoking) and ultrasound lesions of the structure of vascular (carotid and lower limb arteries) walls, such as: (a) hemodynamically nonsignificant stenosis (o50% external carotid and/or lower limb artery diameter reduction); 14,15 (b) marked (0.5-4 mm) intima-media thickness of the carotid artery, measured by means of B-mode ultrasonography; 16 (c) homogeneous or heterogeneous atheroma plaques (43 mm).…”
Section: Laboratory Testing and Echo-duplex Examinationmentioning
confidence: 99%